Public Policies and Sustainable Development in Post-Reform India Regional Responses and the Way Forward - Mishra, Mukunda; Saha, Subrata; Sinha, Madhabendra (New Frontiers in Regional Science: Asian Perspectives, 2023)
XXXVI, 408 p. 1 illus.